Identifikasi Mikroorganisme Yang Ditemukan Di Dalam Cairan Pembersih Lensa Kontak Pada Mahasiswa Fakultas Kedokteran - Denny Habiburrrohman; Tri Umiana Soleha; Ety Apriliana; Dwita Oktaria (MAJORITY, 2020)
The development and use of contact lenses is increasing rapidly, both in developed and developing countries. In line with that many contact lens users are one of the names of infections in the eye. One of the causes is contamination of contact lens solution. To identify the types of microorganisms found in contact lens solutions in students of the Faculty of Medicine, University of Lampung in 2018. This study used a descriptive observational research type. The study was conducted at the Faculty of Medicine, University of Lampung in June 2018. Samples were contact lens solution, with a total sample of 30 samples. The sample was taken to the Laboratory of Microbiology, Faculty of Medicine, University of Lampung. Samples were identified by bacterial culture, gram staining and biochemical tests. Identification of B. subtilis (22%), Pseudomonas aeruginosa (11%), Staphylococcus aureus (8%), Serratia sp (7%), Klebsiella sp (7%), E.coli (2%) . Of the 60 samples studied, it was found that there were no bacterial growths in 26 samples (43%), and there was bacterial growth in 34 samples (57%)